Tatanan Keyakinan Masyarakat Sunda (Sunda Wiwitan) di Era 4.0 - Hisam Ahyani; Jagad Rayana; Ahmad Hapidin (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2021)
The belief system in a society today in an all-digital era can be formed by itself, meaning that the trust of a society is formed naturally. Where the belief system is a way of life that is believed by a community in carrying out its socio-religious life. The Sundanese people as an ethnic group that still exists in Indonesia today have an interesting and unique original belief system, namely Sunda Wiwitan. Sunda wiwitan as a good teaching and can be practiced for the Islamic community, especially in Indonesia in the digital era like today (the era of disruption 4.0) is First, the Sundanese people as one of the second largest tribes in Indonesia after the Javanese, have a pattern and model of Religiosity which is high, interesting and unique which is relevant in the Sunda Wiwitan religion which is still being preserved in the Baduy indigenous peoples in Banten Province and West Java Province. Second, the pattern of religiosity offered by the Sunda Wiwitan community in the 4.0 era included polite attitudes and behavior, and servitude with the term